Impacto do perfil ansioso e dos sintomas de depressão na morbidade e mortalidade de pacientes com síndrome coronariana aguda - Altino, Denise Meira [UNIFESP] (2017)
Objective. Assess the impact of an anxious profile and symptoms of depression on the morbidity and mortality of patients with acute coronary syndrome (ACS) and identify predictive factors for anxiety and depression among these patients. Method. This retrospective cohort study was conducted in two phases in a coronary care unit. The first phase assessed predictive factors for anxiety and depression in 120 patients with ACS. Data were obtained from a previous study’s database. The second phase assessed the morbidity and mortality of 94 patients over a two-year period following hospital discharge. Data were collected from the patients’ electronic medical files and through telephone contact established at three points in time: immediately after hospital discharge; one year after discharge; and two years after discharge. The need to be readmitted due to a cardiovascular disease or the need for myocardial revascularization (MR) was considered for morbidity. Depression and anxiety were assessed using the Beck’s Depression Inventory and the Beck Anxiety Inventory-Trait. The variables collected to identify predictive factors were obtained using an instrument addressing sociodemographic and clinical data. Pearson’s chi-square test, Fisher’s exact test, Likelihood Ratio, the Mann-Whitney, Student’s t-test, and Spearman’s correlation coefficient were used to assess the relationship between anxiety and depression with the study’s variables. Variables associated with p<0.10 in the univariate analysis were used in the fitting of the logistic regression model. To describe the behavior of morbidity and mortality over time in the second phase, the Kaplan-Meier curve was used and the association of survival curves per category of depression and anxiety were compared using the log-rank test. The level of significance adopted was 0.05. The study was submitted to and approved by the Institutional Review Board. Results. Sex, diabetes mellitus, stress, anxiety, obesity, and number of years of education were related to depression. Sex, stress, depression and years of education were related to anxiety. Obesity increased the likelihood of depression by approximately 4.5 times (p-value=0.037) and each added unit in the anxiety score increased the likelihood of depression by 1.2 times (p-value<0.001). Depression, in turn, increased the likelihood of anxiety by 7.9 times (p-value<0.001), while one extra year of education is a protective factor from anxiety (OR=0.874, p-value=0.036). The two-year follow-up showed that 23.4% of the patients had been readmitted after the first year and 12.8% after the second. During hospitalization, 17% underwent a MR, 4.2% of which had one after the first year and none of the patients after the second year. Only 9.6% died in the follow-up period. Depression and anxiety were not related to morbidity or mortality. Conclusion. No significant relationship was found between anxiety and depression and morbidity or mortality. Obesity and anxiety were predictive factors for depression, while depression and fewer years of education were predictive factors for anxiety.